Customary Land Rights Versus Land Use Rights (HGU) - Syamsuddin Pasamai (Interdiciplinary Journal and Hummanity (INJURITY), 2025)
This study discusses the legal conflict between customary rights of customary law communities and the right to use business (HGU) given by the state to third parties, especially large companies. Customary rights as communal rights of indigenous peoples are recognized in a limited way in the Basic Agrarian Law (UUPA), but in practice they are often marginalized by economic interests through the granting of HGU. The research approach used is normative juridical by analyzing relevant laws and regulations, legal doctrines, and court decisions. The results of the study show that the strengthening of HGU in agrarian policies and the weak protection of customary rights trigger land conflicts and social injustice. Therefore, it is necessary to reformulate land policies that are more equitable and in favor of indigenous peoples while still paying attention to the principles of the social function of land as mandated in the UUPA and the 1945 Constitution.